CALIFORNIA SHIELD BEETLE IS A DANGEROUS QUARANTINE PEST OF AN ORCHARD IN THE SOUTH-EAST OF KAZAKHSTAN - Beknazarova Z.; Kopzhasarov B.K.; Dinasilov А.S.; Koigeldina A.E. (Academic Journal of Physical and Chemical Sciences, 2021)
The article presents data on the influence of damage to trees by the California shield on the measurement of growth processes of Apple trees. On trees with a degree of damage of 4 points and covered with shields, cracks were formed, which eventually lead to the suppression of growth processes and the gradual death of trees. Therefore, the California shield should be suppressed as much as possible in the first generation to prevent damage to the fruit. During the research, we used generally accepted methods of plant protection and quarantine. Pheromone traps for catching the California shield were hung during Apple blossom, along the periphery of the tree crowns at a height of 2 m, in the middle rows of the array at the rate of 1 trap per 2 hectares of fruit-bearing garden. Surveys of fruit stands using pheromone traps were carried out only during the summer of males. The traps were checked every 7-10 days, and the pheromone was changed 1 time in mid-summer. The results of observations showed that with the highest degree of infection of trees, which is 4 points, the growth of shoots is reduced compared to a healthy tree by 36.4%, respectively, the leaf surface area is reduced by 38.8%. On trees with a degree of damage of 4 points and covered with shields, cracks were formed, which eventually lead to the suppression of growth processes and the gradual death of trees. According to the data obtained, when trees were populated with 2 points, the percentage of affected apples was 14.3%, when a tree was populated with 3 points, 42.5%, and 55.6% of the fruit was damaged with 4 points. Even if the pest infects 14% of apples, the products are perceived as not standard and not high-quality, so the California shield should be suppressed as much as possible in the first generation to prevent damage to the fruit.